Surgery of Large Skull Base Meningiomas with the External Carotid Artery Ligation: Local Experience - Chaiyabud, Pradit (Journal of Health Science of Thailand, 2018)
The surgery for a large meningioma in the skull base region has high morbidity because of the difficulty to access location and the high vascularity of the tumor. With the recent development of microsurgery techniques and preoperative embolization, the tumor resection is more successful and less morbid. Yet preoperative embolization needs expertise on interventional neuroradiology that few hospitals in Thailand are equipped with. The author presented the experiences in using the ligation of the external carotid artery as an alternative. In a retrospective descriptive study, ten patients with the large skull base meningiomas were treated by the ligation of the external carotid artery before the tumor resection in the same setting. The duration of operation, the completeness of tumor excision, blood loss, and intraoperative neurovascular injury were reviewed. The duration of the operation varied from 2 hours to 5 hours and 20 minutes. All had total removal of the tumors. Units of blood transfusion varied from 0 unit to 4 units . Only one case had an injury to the oculomotor nerve. With local experience, the ligation of the external carotid artery is an useful procedure for the patients with a large skull base meningioma in the setting that preoperative embolization is unavailable.